Tax policy and green sukuk in closing the sustainable finance gap - Radhitiya Wicaksana; Silvia Rahmawati (Institute for Advanced Social, Science, and Sustainable Future, 2025)
Background: Indonesia faces a significant climate financing gap, while existing fiscal instruments have not yet produced consistent reductions in financing costs or clearly measurable environmental outcomes. This study aims to propose an integrated mechanism that links environmental tax revenues with green sukuk, drawing on insights from the literature on green bond governance, risk-premium theory, climate budget tagging, and outcome-based budgeting to address persistent issues of project readiness, investor risk perception, and impact verification. Methods: The study applies a descriptive-analytical approach supported by quantitative modeling using 2018–2024 historical data on carbon tax potential, green sukuk yields, issuance volume, and selected outcome indicators, complemented by a theoretical review of the above frameworks. Findings: The analysis indicates that allocating 0.5–1% of environmental tax revenue into a Green Financing Reserve can reduce perceived risk, potentially lowering yields by 10–25 basis points and expanding issuance capacity, while improving project execution through milestone-based disbursement. This pattern is consistent with the theory that credible risk buffers and verifiable outcomes can compress risk premia and strengthen the causal chain from earmarked revenue to financing efficiency and environmental results (e.g., emission reduction and renewable energy deployment). Conclusion: The Carbon Tax–Backed Green Bond Enhancement Model offers a fiscally disciplined and outcome-oriented framework to enhance both the affordability and effectiveness of green sukuk as a climate financing instrument. Novelty/Originality of this article: This article introduces an integrated model that systematically links carbon tax revenues with sovereign green sukuk risk mitigation through a dedicated fiscal reserve aligned with syariah governance, offering a replicable and evidence-based mechanism for narrowing national climate financing gaps.